In Vitro Activity of Newer Antimicrobials and Relevant Comparators Vs. 349 Stenotrophomonas maltophilia Clinical Isolates Obtained from Patients in Canadian Hospitals (CANWARD, 2011–2016). (4th October 2017) - Walkty, Andrew; Baxter, Melanie; Adam, Heather J; Lagace-Wiens, Philippe; Karlowsky, James; Zhanel, George
Abstract: Background: Stenotrophomonas maltophilia is a non-fermentative gram-negative bacillus that has emerged as an important opportunistic pathogen among hospitalized, debilitated patients. Treatment options for infections caused by this organism are limited because it is intrinsically resistant to antimicrobials from multiple different classes. The purpose of this study was to evaluate the in vitro activity of several newer antimicrobial agents (ceftazidime-avibactam [CZA], ceftolozane-tazobactam [C/T], moxifloxacin [MXF], tigecycline [TGC]) and relevant comparators [e.g., trimethoprim-sulfamethoxazole [TMP-SMX]) against a large collection of S. maltophilia clinical isolates obtained as part of an ongoing national surveillance study (CANWARD, 2011–2016). Methods: From January 2011 to December 2016, inclusive, 12 to 15 sentinel hospitals across Canada submitted clinical isolates from patients attending ERs, medical and surgical wards, hospital clinics, and ICUs (CANWARD). Each center was asked to annually submit clinical isolates (consecutive, one per patient/infection site) from blood (100), respiratory (100), urine (25), and wound (25) infections. Susceptibility testing was performed using broth microdilution as described by CLSI. MICs were interpreted using CLSI breakpoints, where available. Results: 349 S. maltophilia clinical isolates were obtained as a part of CANWARD (86% from a respiratory source). The susceptibility profile of these isolates is presented below. Conclusion: TMP-SMX continues to demonstrate excellent in-vitro activity against S. maltophilia clinical isolates. MXF and TGC may also prove useful in the treatment of infections caused by this pathogen. Disclosures: G. Zhanel, Achaogen: Research relationship, Research support Astellas: Research relationship, Research support Merck Canada: Research relationship, Research support Merck USA: Research relationship, Research support Paratek Pharma: Research relationship, Research support Pharmascience: Research relationship, Research support Sunovion: Research relationship, Research support Tetraphase: Research relationship, Research support The Medicines Co.: Research relationship, Research support Zoetis: Research relationship, Research support